In-Silico Studies of Phytochemicals from Allium sativum with H5N1 Protein in Avian Influenza - Avineet Singh (International Journal of Bioinformatics and Computational Biology, 2024)
Allium sativum or garlic is a medicinal plant that is reported for its applications in many biological activities, such as its antiviral, antidiabetic, and anti-inflammatory properties, etc. In this paper, the focus has been the identification of potential phytochemicals that can be extracted from Allium sativum that can act as a candidate for drug formation that possesses the capability to inhibit the H5N1 Avian Influenza, a type of highly pathogenic and zoonotic strain that poses a major threat to the public health sector. Using the tools provided in the in-silico studies, screening of the 145 phytochemicals from Allium sativum is done against the two major H5N1 proteins, that is, Hemagglutinin and Neuraminidase. The docking results provided along with the result that many compounds have stable interaction with a high binding affinity towards Neuraminidase and Hemagglutinin throughout the stimulation time. These results suggest that phytochemicals from Allium sativum can be promising candidates for the development of therapeutic agents against the H5N1 virus.
Keywords: Allium sativum; Docking; H5N1; HPAI; Schrödinger; garlic